Observation of a Repeated Step-wise Fracture Growth During Hydraulic Fracturing Experiment at the Grimsel Test Site - Dutler, Nathan; Valley, Benoît; Villiger, Linus; Gischig, Valentin; Amann, Florian (My University, 2021)
Hydraulic fracturing (HF) experiments were conducted at the Grimsel Test Site (GTS), Switzerland, with the aim to improve our understanding of the seismo-hydro-mechanical processes associated with high-pressure fluid injection in a moderately fractured crystalline rock mass. Observations from one of these HF experiments indicate simultaneous propagation of multiple fractures during continuous fluid injection. The pressure measured in one observation interval show a cyclic response indicating repeated step-wise fracture growth. This is interpreted as a stick-split mechanism propagating fractures in an episodic manner and connecting them to the natural fracture network. In addition, transient partial closure and opening of fractures on the time-scale of seconds to minutes were observed from pressure and deformation monitoring. Our data set provides unprecedented insight in the complexity of hydraulic fracture propagation.
, 2021